Faktor-Faktor yang Berhubungan dengan Perilaku Pencegahan Keputihan pada Akseptor KB Hormonal di Puskesmas Rawang Barat Tahun 2018 - Cindy Audia Septina; Lita Angelina Saputri; Alsri Windra Doni (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
Leucorrhoea is discharge from the genitalia that is not blood. It is estimated that 75% of women in Indonesia have experienced vaginal discharge. Leucorrhoea will increase by 50% due to the use of hormonal contraception. In Padang City, the coverage of active family planning acceptors is quite high, namely the Rawang Barat Health Center. namely 4,154 (90.59%). The aim of the study was to determine the factors associated with leucorrhoea prevention behavior in hormonal birth control acceptors at the Rawang Barat Health Center in 2018. This type of research was an analytic survey with a cross-sectional design. The population is all active hormonal family planning acceptors with a total sample of 60 people at the Rawang Barat Health Center which was conducted in January-March 2018. The sampling technique was accidental sampling. The research instrument used a questionnaire with bivariate analysis with the Chi Square statistical test. The results showed that 55% of respondents had high knowledge, 51.7% had a positive attitude, 61.7% were less exposed to information about leucorrhoea prevention behavior. Variables that have a relationship with leucorrhoea prevention behavior are knowledge (p=0.000), attitude (p=0.000), while variables that are not related are information exposure (p=0.432). Conclusion: there are still respondents with low knowledge, attitudes, and information exposure. It is suggested that there is a need for more explanation and explanation regarding leucorrhoea in the form of counseling by health workers.